PEMBELAJARAN IPS BERBASIS KEARIFAN LOKAL - Iyan Setiawan; Sri Mulyati (Jurnal Ilmiah Pendidikan Dasar, 2020)
ABSTRACTOne problem of students in school is seen from the indifference to the environment. Students are often confronted with reality or facts in their environment, with not many questioning these environmental problems. Environmental problems such as scattered garbage, floods, forest fires and the environment which are considered as natural occurrences, can be considered as problems faced by students in their lives. Local wisdom-based learning is a solution to increase the intelligence of students to always be close to the concrete training that they face daily. Efforts to draw green behavior can be applied in the learning process by using learning models that are in line with dialogic learning patterns. With another understanding, to improve ecological intelligence students need to be supported by critical pedagogy, namely by improving awareness to change reality. The research method used is the method of library research / study of literature and data analysis techniques used are content analysis. From the results of the discussion it can be concluded the value of local cultural wisdomKeywords: social studies learning; ecological intelligence.